Flo[RA]: Uma aplicação móvel para comunicar ciência através do lúdico e da realidade aumentada - David Jorge Lourenço Soares (2021)
At a time when the supply of content is greater than the time we have to consume it, it is necessary to find solutions and strategies that capture the attention and motivate users. These strategies are particularly important for museum spaces that increasingly need to innovate and create more interaction and interest in their spaces. This dissertation focuses on understanding how we can contribute to the communication of science through an application with ludic elements and augmented reality, but also good usability practices for this type of applications. For this, a mobile application was developed that allows visitors to have a ludic activity and with augmented reality in a botanical exhibition of the Biodiversity Gallery and later another in the Botanical Garden of Porto. At the end, they can place in augmented reality images of tree leaves that they previously collected, being able to create visual compositions that can be saved or shared, promoting dialogue and a sense of belonging to the scientific object. Data on its development, the technologies used, implementation procedures and some usability best practices are presented. Tests were conducted with usability and the botanical garden specialists, and user opinions were collected that helped redesign the application and understand the contribution of this type of application in science communication, but also with suggestions that can contribute to future work. The results were promising, showing a great need for applications of this kind for science communication in these museum spaces.